A Numerical Study on the Utilization of Small-Scale Model Testing for Slope Stability Analysis - Minghua Wang; Xiaoliang Wang; Guoqiang Fu; Mi Zhou; Jian Chen (Buildings, 2025)
Small-scale model tests have been used widely to examine the behavior of slopes. When all similarity principles are conformed, the test results can be translated to the behaviors of slopes in the prototype. However, when the similarity principles cannot be fully conformed, the model test results need to be interpreted. The interpretation of the slopes stability behaviors from the small-scale model test under non-conformity conditions to that of the prototype is investigated, considering various slope scales and soil properties, undertaken through the finite element (FE) method conducted by the ABAQUS package. Prior to conducting the finite element (FE) parametric study, the numerical results were verified by comparing them with data from previous studies, with good agreement obtained. According to the findings from the parametric study, a framework was developed to allow the 1 g model-scale test results to be translated to the parameters used for the prototype slope design. The study examined both the sliding surfaces and the safety factors of slopes to establish a connection between model tests and their full-scale counterparts. This framework provides a means to effectively utilize 1 g of small-scale test data for designing and analyzing prototype slopes.